2004
DOI: 10.2466/pms.98.2.371-381
|View full text |Cite
|
Sign up to set email alerts
|

Expertise and Peripheral Autonomic Activity during the Preparation Phase in Shooting Events

Abstract: This study compared effectiveness of the concentration period in two groups of shooters to evaluate the influence of their expertise while concentrating on the target. Marksmen (pistol shooters, 10 men and 5 women) and pentathletes (6 men and 7 women) took part in a shooting competition in keeping with the rules of each event. Participants were then asked to imagine themselves shooting, at the laboratory. Five variables representing the activity of the autonomic nervous system were continuously recorded (skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 20 publications
(19 reference statements)
2
11
2
Order By: Relevance
“…Such autonomic responses were shown to disappear when athletes had difficulties with motor imagery or in the event of many successive repetitions (Roure et al 1999;Guillot et al 2004b). Conversely, recording skin resistance response during motor imagery attests to mental operation of movement representation during each trial (Deschaumes-Molinaro et al 1991;Guillot et al 2004a). Therefore, these results indicate that muscle fatigue does not affect motor imagery accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such autonomic responses were shown to disappear when athletes had difficulties with motor imagery or in the event of many successive repetitions (Roure et al 1999;Guillot et al 2004b). Conversely, recording skin resistance response during motor imagery attests to mental operation of movement representation during each trial (Deschaumes-Molinaro et al 1991;Guillot et al 2004a). Therefore, these results indicate that muscle fatigue does not affect motor imagery accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Bradycardia is usually recorded during motor imagery (Deschaumes-Molinaro et al 1991;Guillot et al 2004a) and may be correlated to an increase in focused attention (Lacey and Lacey 1974), thus attesting to mental work. However, in the present study, heart rate was not aimed to attest mental processes, because of the energetic expenditure elicited by physical exercise, but was recorded as an indicator of physical activity intensity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it can be conjectured that in order to be regarded as a specific effect, the degree of autonomic activation during mental imagery should be proportional to the imagined effort (Decety, Germain, Pastene, & Jeannerod, 1991). Deschaumes-Molinaro et al (1991) and Guillot et al (2004) showed that similar autonomic responses in an attentionally engaging task (shooting events) occur during real and imagined attempts. In a group of subjects requested to imagine swimming over a distance of 100 m, Beyer, Weiss, Hansen, Wolf, and Seidel (1990) reported that respiratory frequency and heart rate increased during mental imagery.…”
Section: Phasic Response During the First Behavioral Phasementioning
confidence: 97%
“…By comparing ANS variable responses during the preparation phase both in real and mental rehearsal attempts, Deschaumes-Molinaro, Dittmar, and Vernet-Maury (1991) evidenced similar autonomic responses in a group of athletes (marksmen). Moreover, Guillot, Collet, Molinaro, and Dittmar (2004) concluded that the same motor program is involved both during the actual preparation period, and during mentally simulated attempts in an attentionally engaging task (i.e. shooting events).…”
mentioning
confidence: 98%